Oncogenic p53 triggers amyloid aggregation of p63 and p73 liquid droplets - Elaine C. Petronilho; Guilherme C. de Andrade; Gileno dos S. de Sousa; Fernando P. Almeida; Michelle F. Mota; Ana Vitória dos S. Gomes; Carlos Henrique S. Pinheiro; Mylena C. da Silva; Hiam R. S. Arruda; Mayra A. Marques; Tuane C. R. G. Vieira; Guilherme A. P. de Oliveira; et al. (Communications Chemistry, 2024)
Abstract P53 Phase separation is crucial towards amyloid aggregation and p63 and p73 have enhanced expression in tumors. This study examines the phase behaviors of p53, p63, and p73. Here we show that unlike the DNA-binding domain of p53 (p53C), the p63C and p73C undergo phase separation, but do not form amyloids under physiological temperatures. Wild-type and mutant p53C form droplets at 4°C and aggregates at 37 °C with amyloid properties. Mutant p53C promotes amyloid-like states in p63C and p73C, recruiting them into membraneless organelles. Amyloid conversion is supported by thioflavin T and Congo red binding, increased light scattering, and circular dichroism. Full-length mutant p53 and p63C (or p73C) co-transfection shows reduced fluorescence recovery after photobleaching. Heparin inhibits the prion-like aggregation of p63C and p73C induced by p53C. These findings highlight the role of p53 in initiating amyloid aggregation in p63 and p73, opening avenues for targeting prion-like conversion in cancer therapy.